Socioeconomic factors that influence adolescents' perception of sexuality, motherhood and abortion (Research, Society and Development, 2021)
The aim was to analyze perceptions about sexuality, motherhood and abortion, according to socioeconomic factors in adolescents aged 15 to 19 years, high school students, in the Greater Vitoria Metropolitan Region - Espirito Santo, Brazil. Cross-sectional school-based study with 2,292 students, carried out in 2016/2017, through a structured interview. The instrument “Questionnaire of Values and Beliefs about Sexuality, Maternity and Abortion” was used, which has five dimensions: pleasure, affectivity, reproduction, motherhood and abortion. For the analyzes, we used: mean, standard deviation, ANOVA and multiple linear regression. There was a predominance of agreement for the perceptions about the functions of sexuality, disconnection from motherhood as the main function of the female condition and negative perceptions about abortion. In the regression, the maternity dimension was the most explained by socioeconomic factors (R² = 6.7%): age 18/19 years (β = 0.154), male gender (β = 0.154), 2nd and 3rd years of high school (β = -0.118; -0.172), marital status (β = -0.341), having paid work (β = 0.113), head of the family with secondary education or higher (β = -0.234; -0.246) and total family income> 3 wages (β = -0.234). Adolescents' perceptions are influenced by socioeconomic factors, with socioeconomic inequalities being important markers for these perceptions.